School-Village-Family Collaboration in Strengthening Religious Moderation at Kaliputih Elementary School - Siti Lailiyah; Raharjo; Mustopa; Atiqoh (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2026)
This study examines school-village-family collaboration in strengthening religious moderation at Kaliputih Elementary School. Previous studies on religious moderation in schools have mostly focused on curriculum, character education, and school culture, while the collaborative relationship between schools, village government, and families remains underexplored. This study used a qualitative case study design. Data were collected through observation, in-depth interviews, and documentation involving school actors, village government representatives, and parents. The data were analyzed thematically to identify actor roles, collaboration mechanisms, and qualitative indicators of religious moderation practices. The findings show that the school internalizes moderation values through learning, teacher role modeling, and inclusive activities. The village government provides social legitimation through community-based activities and support for harmony. Families reproduce these values through parenting practices and daily habituation. The novelty of this study lies in explaining religious moderation as a collaborative practice across school, village, and family contexts. ABSTRAK Penelitian ini mengkaji kolaborasi sekolah, desa, dan keluarga dalam memperkuat moderasi beragama di SDN Kaliputih. Kajian sebelumnya tentang moderasi beragama di sekolah umumnya berfokus pada kurikulum, pendidikan karakter, dan budaya sekolah, sedangkan hubungan kolaboratif antara sekolah, pemerintah desa, dan keluarga masih belum banyak dikaji. Penelitian ini menggunakan desain studi kasus kualitatif. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi yang melibatkan pihak sekolah, perwakilan pemerintah desa, dan orang tua. Data dianalisis secara tematik untuk mengidentifikasi peran aktor, mekanisme kolaborasi, dan indikator kualitatif praktik moderasi beragama. Temuan menunjukkan bahwa sekolah menginternalisasi nilai moderasi melalui pembelajaran, keteladanan guru, dan kegiatan inklusif. Pemerintah desa memberi legitimasi sosial melalui kegiatan berbasis komunitas dan dukungan terhadap kerukunan. Keluarga mereproduksi nilai tersebut melalui pola asuh dan pembiasaan harian. Kebaruan penelitian terletak pada penjelasan moderasi beragama sebagai praktik kolaboratif lintas sekolah, desa, dan keluarga.